Design and synthesis of dual-band microwave bandpass filter based on hybrid polynomials - Zee, E. (Electromagnetics Academy, 2017)
This paper presents a method of designing a bandpass filter using hybrid polynomials. Two different approaches are discussed in this paper. The first method uses class hybridization of a lowpass Chebyshev and highpass maximally flat to achieve the hybrid filtering function (HFF). The second method employs both Chebyshev polynomials of the first and second kinds to form a modified Chebyshev polynomial. Both methods achieve a narrowband dual-band lowpass prototype (DBLPP) without much deviation from classical methods of synthesis. The designs can be adapted into a modified interdigital prototype which will be shown in this paper. The results and measurements reflect a good adherence to the theoretical calculations. © 2017, Electromagnetics Academy. All rights reserved.